2022
DOI: 10.3201/eid2802.211532
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Spread of Severe Fever with Thrombocytopenia Syndrome Virus by Parthenogenetic Asian Longhorned Ticks

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is spreading rapidly in Asia. This virus is transmitted by the Asian longhorned tick ( Haemaphysalis longicornis ), which has parthenogenetically and sexually reproducing populations. Parthenogenetic populations were found in ≥15 provinces in China and strongly correlated with the distribution of severe fever with thrombocytopenia syndrome cases. However, distribution of these cases was poorly correlated with the distribution of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…Similar to the results of previous studies [ 16 , 18 – 20 , 26 , 27 ], most SFTS cases occurred from April to October. The seasonal distribution of SFTS cases might relate to tick dynamics [ 28 30 ]. Ticks were reported as the carriers and vector host of SFTSV, of which H. longicornis were the predominant population carrying SFTSV [ 11 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of previous studies [ 16 , 18 – 20 , 26 , 27 ], most SFTS cases occurred from April to October. The seasonal distribution of SFTS cases might relate to tick dynamics [ 28 30 ]. Ticks were reported as the carriers and vector host of SFTSV, of which H. longicornis were the predominant population carrying SFTSV [ 11 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the potential natural circulation of SFTSV in the urban setting, we carried out field surveys on small mammals and parasitic ticks at two locations in Beijing City in 2021, one small park surrounded by up-market gated communities in Shunyi District and the Olympic Forest Park in Chaoyang District, where parthenogenetic H. longicornis ticks were discovered in a previous survey in 2019 (Fig. 6A)(X. Zhang et al, 2022).…”
Section: The Susceptibility Of Hedgehogs To Experimental Infection With Sftsvmentioning
confidence: 99%
“…(B) Phylogenetic analysis of the parthenogenetic population of Asian long-horned ticks. Maximum likelihood tree was established with the mitochondrial genomes of H. longicornis collected in Chaoyang District and Shunyi District (Chaoyang DistrictP2, accession number, OL335942 and ShunyiDistriceP1 accession number, OL335941) (red) and from SFTS endemic areas(X. Zhang et al, 2022).…”
Section: The Susceptibility Of Hedgehogs To Experimental Infection With Sftsvmentioning
confidence: 99%
See 1 more Smart Citation
“…The parthenogenetic reproductive ability of H. longicornis allows a single female tick to reproduce asexually without fertilization of her embryos. Comparisons of bisexual and parthenogenetic tick populations have suggested that parthenogenetic ticks have a higher dispersal capacity in nature than their bisexual counterparts, and this dispersion can be facilitated by migratory birds (Zhang et al, 2022). H. longicornis is adaptable to a wide range of climates across its native and invasive ranges, including seasonal climates.…”
Section: Introductionmentioning
confidence: 99%